The Fabrication and Testing of Unmanned Aerial Vehicle (UAV) Wing Structure Using 3D Printing and Carbon Fibre Skinning Method - Mohd Kamarulnizam, Muhammad Ariff Nazrin; Yaakub, Mohd Fauzi (Progress in Aerospace and Aviation Technology, 2024)
This study examines the efficacy of integrating 3D printing with carbon fibre skinning to construct wing structures for Unmanned Aerial Vehicles (UAVs). The primary objective is to enhance the structural integrity and material characteristics. The study performs static load tests, which demonstrate that wings reinforced with carbon fibre lamination can endure a substantially greater maximum stress of 29.43 N, in contrast to 14.391 N for wings produced only by 3D printing. The carbon fibre laminated wings have a greater load-bearing capability, as evidenced by the safety factor study. This analysis reveals that the permitted loads for carbon fibre laminated wings (19.61 N) are higher compared to 3D printed wings (9.594 N). The tensile testing of the specimens reveals that carbon fibre laminated wings demonstrate enhanced ductility, stiffness, and yield strength. Additionally, they withstand greater levels of maximum stress and strain, except for a slightly higher stiffness seen in 3D printed wings. This research highlights that carbon fibre laminated wings are typically more durable and versatile for many uses, although 3D printed wings may be favoured in situations when greater rigidity is necessary. In conclusion, the study effectively showcases the advantages of combining 3D printing with carbon fibre skinning in the construction of UAV wings. This research significantly contributes to the progress of UAV design and provides fresh insights in the fields of aeronautical engineering and materials science. It is particularly valuable for applications that require UAVs with exceptional performance, durability, and reliability.